Assessing Africa Readiness to Host Travelers with Disabilities: A Review of Accessible Accommodation Studies in African Countries - Kara, Nasra (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2022)
Even though Africa has been involved in the movement towards protecting the rights of disabled people, the emerging market is still under-served. Despite having multiple tourist attractions, the continent has not fully implemented its tourism and disability policies to make sure that barrier-free accommodation services are offered to disabled guests. The purpose of this study was to review and analyze studies done on the accommodation sector in African countries and to establish the extent to which the existing accommodation establishments were user-friendly to disabled people. Google Scholar, EBSCOhost, and science direct were used to generate academic journals. Two main themes mainly demand and supply was developed from the content analysis. On the demand side, quality of services and user-friendly services were the main challenges limiting the accommodation sector from offering barrier-free services to disabled guests while on the supply side, accessible room facilities were seen as a critical issue. Hotel service providers needed to make sure that there were accessible facility in bar and restaurant including ramps, elevators, hearing aids, leveled access routes as well as spacious rooms to host disabled guests. Provision of barrier-free services as recommended in the social disability model would be possible if service providers were willing to change their attitude regarding disability. Once the attitude is changed then it would be easy to resolve the structural and communication barriers.